Heel blood sampling in preterm infants: which technique?. Issue 3 (November 1994) - Barker, D P; Latty, B W; Rutter, N
Abstract : Preterm infants undergoing heel blood sampling were randomly allocated to specimen collection by heel puncture (Autolet II Clinisafe) or incision (Tenderfoot 'preemie'). A total of 187 procedures was observed in 47 infants. No significant difference was found in the infants' behavioural response, increase in heart rate, or in the frequency of specimen haemolysis. Collection times for small to medium sized samples were similar, but for large samples (> 1 ml) the Tenderfoot method was superior and fewer repeat procedures were necessary. Tenderfoot has the added advantage of improved safety, but it is too costly for routine use.